STUDY ON THE INFLUENCE OF HYDRAULIC BULGING RESTRAINT INTENSITY ON MICROSAMPLE OF MAIN PIPELINE MATERIAL - WANG ChunHui; AN YingHui (Jixie qiangdu)
Three kinds of micro-sample thicknesses(0.4 mm,0.5 mm and 0.6 mm)and three kinds of chamfer radii(0.5 mm,0.8 mm and 1.0 mm)of the original main pipe material were taken as the research objects to analyze the influence of restraint intensity in hydraulic bulging test,and to build a correlation model of yield strength,tensile strength and hydraulic bulging elongation.The fitting error of yield strength and tensile strength and the dispersion of hydraulic bulging elongation were studied.The results show that with the gradual increase of microspecimen thickness,the peak load increases obviously,while the peak displacement generally decreases,but the overall curve trend changes little.With the gradual decrease of the microsample chamfer radius,the peak displacement decreases obviously.The test stability is best under the test conditions of microsample thickness 0.5 mm and chamfer radius 1.0 mm.